The K‑Region in Pyrenes as a Key Position to Activate Aggregation-Induced Emission: Effects of Introducing Highly Twisted N,N‑Dimethylamines - Sasaki, Shunsuke; Suzuki, Satoshi; Igawa, Kazunobu; Morokuma, Keiji; Konishi, Gen-ichi (Journal of organic chemistry, 2017)
A new design strategy to activate aggregation-induced emission (AIE) in pyrene chromophores is reported. In a previous report, we demonstrated that highly twisted N,N-dialkylamines of anthracene and naphthalene induce drastic AIE when these donors are introduced at appropriate positions to stabilize the S1/S0 minimum energy conical intersection (MECI). In the present study, this design strategy was applied to pyrene: the introduction of N,N-dimethylamine substituents at the 4,5-positions of pyrene, the so-called K-region, are likely to stabilize MECIs. To examine this hypothesis, four novel pyrene derivatives, which contain highly twisted N,N-dimethylamino groups at the 4- (4-Py), 4,5- (4,5-Py), 1- (1-Py), or 1,6-positions (1,6-Py) were tested. The nonradiative transitions of 4,5-Py are highly efficient (k nr = 57.1 × 107 s–1), so that its fluorescence quantum yield in acetonitrile decreases to Φfl = 0.04. The solid-state fluorescence of 4,5-Py is efficient (Φfl = 0.49). In contrast, 1,6-Py features strong fluorescence (Φfl = 0.48) with a slow nonradiative transition (k nr = 11.0 × 107 s–1) that is subject to severe quenching (Φfl = 0.03) in the solid state. These results underline that the chemistry of the pyrene K-region is intriguing, both from a photophysical perspective and with respect to materials science.